Tratamento clínico da Leishmaniose Tegumentar Americana canina com furazolidona e domperidona - Passos, Stela Rechinelli (2014)
American Cutaneous Leishmaniasis (ACL) is a public health problem in countries of sub-tropical America. Euthanasia of dogs affected is not obligatory as in visceral leishmaniasis, though treatment with drugs for human treatment is prohibited and there is no treatment recommended. The aim of this study was to evaluate the efficacy of treatment with furazolidone and domperidone in dogs symptomatic for ACL caused by Leishmania (Viannia) braziliensis. Confirmation of infection was performed by PCR and parasite culture from tissue collected from lesion limit. After adaptation period of 60 days, the animals were divided into a control group (n = 4) and treated group (n = 8). The treated group received furazolidone treatment for 21 days interspersed with domperidone for 10 days. The dogs that showed no lesion remission during this period received again the same treatment cycle up to 93 days. Among the eight treated animals, one dog showed no one lesion remission after treatment. All animals were observed for 12 months after treatment. There was no recurrence of injury to the animals in it was forgiveness, neither self-healing in the control group during this period. The animal that had no wound healing showed reduction of injury measures after treatment. Our data suggest that furazolidone and domperidone administration is effective for wound healing of symptomatic dogs for ACL caused by L. (V.) braziliensis.